PERLINDUNGAN KONSUMEN PENERIMA MANFAAT ASURANSI PERTANGGUNGAN JIWA ATAS POLIS YANG DINYATAKAN LAPSE SECARA SEPIHAK PASCA DIAJUKAN KLAIM (STUDI KASUS PUTUSAN NOMOR 628 PDT.G/2019/PN.JKT.BRT) - Ruth Yaniasni Leonita; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2020)
The purpose of this study is to determine the form of legal protection for consumers who receive life insurance benefits for policies declared unilaterally lapse after the claim is submitted and from the perspective of the insurance company PT. Panin Dai-Ichi Life for providing information on policy status that was declared lapse. The results of the study showed that the form of legal protection for insurance consumers in this case was preventive and repressive protection. Preventive through mediation to BMAI, and repressive through court lawsuits. In his lawsuit, the judge has won the consumer, but there is an appeal so that consumers have not received legal protection for compensation. In addition, external protection through the Consumer Protection Act and internal protection through insurance policies. However, the Consumer Law was unable to ensnare PT. Panin Dai-Ichi  Life for violating Article 4 letter c and Article 7 letter b has no legal sanction. Likewise, internal protection can be seen from the insurance policy if the lawsuit for violating Article 18 Paragraph (1) letter f regarding standard clauses is proven proven, then the business actor based on Article 62 Paragraph (1) may be subject to imprisonment and fines. Thus it can be concluded that through external protection the Consumer Protection Act, in this case it has not been able to protect consumers.